2001
DOI: 10.1115/1.1430237
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Model for Tapping Process With Emphasis on Process Faults and Hole Geometry

Abstract: A mechanistic approach for modeling the tapping process is presented. A methodology for computing chip load is developed for an arbitrary tap geometry. The mechanics of cutting for tapping is analyzed, considering it as an oblique cutting phenomenon. The effects of tap geometry (tap diameter, thread pitch, number of flutes, flute helix angle, tooth rake angle, and thread type), workpiece geometry (hole diameter and hole depth), process parameters (spindle speed and tap penetration depth), and process faults (t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 7 publications
0
23
0
2
Order By: Relevance
“…130 The threaded parts are primarily used for force transmissions; the assurance of safety in force transmission depends notably on the quality of the threads, which in turn is dependent upon the nature of the cutting process. 131 ' 132 The cutting fluid is more important in tapping than it is in most other machining operations because the cutting edges are more susceptible to damage by heat and the chips have more chance of being trapped in the flute. The application of coatings to taps used for high-speed tapping becomes necessary in order to improve their performance in the face of difficulties with cooling, and dealing with a high volume of removal over short periods of time.…”
Section: Tapping Operationsmentioning
confidence: 99%
“…130 The threaded parts are primarily used for force transmissions; the assurance of safety in force transmission depends notably on the quality of the threads, which in turn is dependent upon the nature of the cutting process. 131 ' 132 The cutting fluid is more important in tapping than it is in most other machining operations because the cutting edges are more susceptible to damage by heat and the chips have more chance of being trapped in the flute. The application of coatings to taps used for high-speed tapping becomes necessary in order to improve their performance in the face of difficulties with cooling, and dealing with a high volume of removal over short periods of time.…”
Section: Tapping Operationsmentioning
confidence: 99%
“…The filling of cutting mouths makes the cutting operation difficult and causes breakage of the cutting tool. 11,13 When Figure 7 was examined for the M5 and M6 taps, it was seen that the best tool-life results were obtained with the M6 taps. The effect of Q value was seen clearly for both the cutting tools.…”
Section: Resultsmentioning
confidence: 99%
“…11,13,18 In stainless steels, higher ductility makes the machinability difficult. In tapping, the material build-up-edge to the cutting mouths causes squeezing.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is shown that the total tapping load consists of a load resulting from the chip formation and tool flank friction, and a chip packing load, random in nature, resulting from chip clogging in the flute. Dogra et al [6] analyzed a mechanistic torque and thrust model for the tapping process. The basic concept involved in that model is that the elemental cutting and thrust forces acting on each tooth are proportional to the uncut chip area.…”
Section: Introductionmentioning
confidence: 99%